Attitudes Of Jordanian Students Toward Managers' Leadership Styles And Their Relationship To The National Culture - Sulieman, Moyaid (Journal of Applied Business Research, 2017)
This study explores the attitudes of a group of university students about managers' leadership styles and the cultural characteristics of the Jordanian society. The amount of research on the topic of leadership styles in Jordan is rare, particularly when associated with national culture. The outcomes demonstrated that the surveyed students were more disposed to portray the proposed leadership styles of managers as Team management style followed by Country Club style. On the other hand, when these students were asked to describe their national culture, they described it in a way similar to the Arab Group culture presented by Hofstede. Furthermore, the surveyed students gave power distance then muscularity the first confirmation. No significant relation observed between students' attitudes of leadership styles and characteristics of the Jordanian culture. Reasons for this outcome together with a few recommendations are incorporated into this study.
Keywords: Jordanian National Culture; Students' Attitude; Managers’ Leadership Styles